Comparative ozone production sensitivity to NOx and VOCs in Quito, Ecuador, and Santiago, Chile - M. Cazorla; M. Trujillo; R. Seguel; R. Seguel; L. Gallardo; L. Gallardo (Atmospheric Chemistry and Physics, 2025)
Amid the current climate and environmental crises, cities are being called to reduce levels of atmospheric pollutants that also act as short-lived climate forcers, such as ozone and PM2.5. This endeavor presents new challenges, especially in understudied regions. Here, we use a chemical box model to investigate ozone production sensitivity to NOx and VOCs in Quito, Ecuador, and Santiago, Chile. We present ozone production rates (P(O3)) calculated using VOC measurements taken in Santiago, along with VOC vs. CO linear regressions (LRs), and complement the analysis with Monte Carlo (MC) simulations. In Quito, VOC measurements are unavailable. We therefore simulated a range of VOC concentrations using LRs and MC simulations. We modeled P(O3) in March 2021 and for typical conditions per season in 2022. We calculated a range of P(O3) in Quito of 15–50 ppbv h−1 year-round. In Santiago, we found that P(O3) is 23–50 ppbv h−1 in the ozone season (austral summer). Although the P(O3) magnitudes were found to be comparable, Santiago has a well-established ozone season, unlike Quito where concentrations are lower. From sensitivity experiments, alkenes and aromatics contribute 50 % to P(O3) in Santiago and could reach 70 %–90 % in Quito (noon and afternoon). Aldehydes and ketones contribute 30 %–40 % in Santiago and about 20 % in Quito (noon and afternoon). We estimate the isoprene contribution to be 20 % in Santiago and 10 % in Quito. VOC reduction experiments generally lowered P(O3) in both cities. In Santiago, NOx reductions increased the morning P(O3).